Application Value of Metagenomics Next-Generation Sequencing (mNGS) in Detection of Mucormycosis after Chemotherapy in Childhood Acute Leukemia. (19th August 2022) - Li, Wenzi; Zhu, Hua; Wen, Li; Quan, Meijie; Wang, Li
Abstract : Objective . To analyze the application of macrogenomics next-generation sequencing (mNGS) in the detection of postchemotherapy trichomoniasis cases in children with acute leukemia. Methods . To retrospectively analyze the clinical data of 7 patients with acute leukemia combined with trichomoniasis after chemotherapy in the department of hematology and oncology of Hebei Children's Hospital, and to summarize the characteristics of their postchemotherapy clinical data, diagnostic and therapeutic processes, and outcomes. Results . Among the 7 children, 6 cases had acute lymphoblastic leukemia and 1 case had acute myeloid leukemia. mNGS detected trichoderma infection, including 1 case of pulmonary cerebral type and 6 cases of pulmonary type. After treatment, 1 case died, 2 cases were cured, and 4 cases improved. Conclusion . The clinical manifestations of trichomoniasis after combined chemotherapy in pediatric acute leukemia lack specificity. Early application of the mNGS assay is of great value.